Evaluation of GPR Detection for buried objects material with different depths and scanning angles. Issue 1 (March 2021) - Alshamy, Hussain M.; Abdul Sadah, Jafar W.; Saeed, Thamir R.; Mohammed, Shaymaa A.; Hatem, Ghufran M.; Gatan, Assel H.
Abstract: A Ground-penetrating radar (GPR) is considered an efficient non-destructive device for detecting the buried object. The GPR operation is based on the analysis of the received scattered of the transmitted signal. Its output is the two-dimensional image radiogram hyperbolic curve, this image represents the reflected signal of the buried object. To date, studies investigating targets (buried objects) have produced equivocal results. Therefore, this paper highlights the importance of the effect of changing target-detection parameters (material type, target to surface distance, size, and scan to target location angle) concerning the hyperbolic curve on the GPR experiment image. A practical model has been built for this experiment with three material types (metal, plastic, and pottery) that are buried in the sand soil. Three tests have been done for different types of material, in the different depth for each buried object of the same material. Then, changing the size of the buried object (small and big size), also, changing the location angle of the buried objects concerning the direction of the GPR scan. For these tests, the effect on the hyperbolic curve has been recognized. A MALA 1 GHz geophysical GPR system is used in these experiments. As a result, the strength of the reflected EMW changes concerning the type of material, size, depth, and location angle of the buried object.